Liver imaging : MRI with CT correlation - Altun, Ersan, 1975-; El-Azzazi, Mohamed; Semelka, Richard C. (Chicester, West Sussex, UK ; Hoboken, NJ : John Wiley & Sons Inc., 2015)
"This book provides a practical approach for imaging of focal and diffuse liver lesions based on state-of-the-art MR and CT imaging sequences, multidetector row CT images, 3D reformatted images, breath-hold MRI sequences, and cutting-edge MR 3T images where appropriate, concise but useful figure legends, relevant and systematic (differential) diagnostic information, the latest references to primary literature and clinical evidence, and patient management possibilities"--Provided by publisher.
Transcatheter arterial chemoembolizationAblative therapies; References; Chapter 16 Liver Trauma; References; Index; EULA.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Liver -- Diseases -- Magnetic resonance imaging; Liver -- Diseases -- Tomography; Liver Diseases -- diagnosis; Diagnosis, Differential; Imaging, Three-Dimensional.; Magnetic Resonance Imaging; Tomography, X-Ray Computed; Liver -- Imaging; Liver -- Magnetic resonance imaging; Radiographic contrast media; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Electronic books